Pertanggungjawaban Pidana Korporasi terhadap Pencemaran Lingkungan : Studi Kasus Masyarakat Hinkley, California Melawan Pacific Gas and Electric Company - Savitri, Ayu; Jannah, Rahmatul; Aurella, Lois Salwa; Rakha, Agung; Firdaus, Muhammad Razaq (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The environmental pollution case that occurred in Hinkley, California, by Pacific Gas and Electric Company (PGE) is one of the most serious examples of environmental law violations, causing significant health and social impacts on the community. This paper examines corporate criminal liability for environmental pollution crimes by reviewing the PGE case as the primary study. This research employs a normative juridical method with a conceptual and case-study approach. The analysis shows that corporate criminal liability must be strictly enforced, as PGE’s actions meet the elements of an environmental crime that resulted in widespread public harm. This study also provides a comparison of corporate criminal law principles applied in the United States and Indonesia.